LEARNERS’ NEED ANALYSIS OF ENGLISH FOR SPECIFIC PURPOSES OF CULINARY DEPARTMENT STUDENTS AT SMKN 3 KOTA BENGKULU - Annisa Ayutami; Alamsyah Harahap; Syahrial . (Journal of English Education and Teaching, 2018)
The design of this research is qualitative descriptive research. The purposes of this research are first to analyze the English learning needs of students in Culinary Department and second to identify what are the needs that not available in the textbook used. The subjects of this research are first the students of SMKN 3 Bengkulu 10th grade, second the English   teachers   who   teach   at   the   Culinary   department,   third   alumni   of   Culinary department, and fourth the English language users in the field of Culinary. In this study, researchers used the needs analysis to find what are the needs and wants of students in learning English. The instruments that used in this study are questionnaires, interview questionnaires, and textbooks used in English language learning. The result of the research indicates that the students' English needs is the learning material according to their vocation and the activity that can make the students more active in the learning process. For unavailable needs are including the materials that contain more vocabulary related to culinary, text examples and tasks to suit students' abilities, and learning activities that can make students more active.